Exploring Linguistic Distinctions: A Comparative Analysis of Baduy and Priangan Sundanese Lexical Choice - Rahayu, Sri; Kurniawan, Eri; Isnendes, Retty; Ramadani, Ramadani (Ranah: Jurnal Kajian Bahasa, 2025)
This study aims to analyze lexical variation between Baduy and Priangan Sundanese and to explain how sociocultural factors shape lexical choices, language use, and speaker identity. A qualitative approach with a descriptive–comparative design was employed. Data were collected through observation, interviews, natural conversation recordings, and document analysis involving native speakers in Kanekes (Baduy) and the Priangan region (Bandung, Tasikmalaya, Garut, and Cianjur). The data were analyzed through data reduction, comparative data display, and lexical analysis using theoretical frameworks from contact linguistics and ecolinguistics to examine the influence of isolation, modernization, and language contact.The findings reveal that Baduy Sundanese preserves archaic vocabulary (e.g., kula, kakang), distinctive particles (mah, pan, teh), and specific semantic distinctions, such as the meaning of saung as a primary dwelling. In contrast, Priangan Sundanese reflects modernization and codification through the use of more standardized forms and stronger influence from Indonesian. Additional differences were observed in phonology (vowel lengthening), morphology (retention of traditional derivational forms), syntax (frequent subject/object omission), and levels of Indonesian interference. Sociocultural factors underlying these variations include the geographical isolation of the Baduy community, strong adherence to tradition, politeness norms, and the Priangan community’s openness to modern education and external contact. Overall, lexical choices function as markers of linguistic identity: the Baduy community demonstrates linguistic conservatism as a form of resistance to homogenization, whereas Priangan speakers exhibit adaptation to modernity. These findings contribute to studies on Sundanese variation, contact linguistics, and ecolinguistics, while supporting efforts to preserve endangered dialects. Abstrak Penelitian ini bertujuan menganalisis variasi leksikal antara Bahasa Sunda Baduy dan Priangan serta menjelaskan pengaruh faktor sosiokultural terhadap pilihan leksikal, penggunaan bahasa, dan identitas penuturnya. Penelitian menggunakan metode kualitatif dengan desain deskriptif-komparatif. Data dikumpulkan melalui observasi, wawancara, perekaman percakapan alami, dan studi dokumen yang melibatkan penutur asli di Kanekes (Baduy) dan wilayah Priangan (Bandung, Tasikmalaya, Garut, dan Cianjur). Data dianalisis melalui reduksi data, penyajian data dalam tabel komparatif, serta analisis leksikal berbasis teori linguistik kontak dan ekolinguistik untuk menelusuri pengaruh isolasi, modernisasi, dan kontak bahasa. Hasil penelitian menunjukkan bahwa Bahasa Sunda Baduy mempertahankan kosakata arkais seperti kula dan kakang, partikel khas seperti mah, pan, dan teh, serta sejumlah perbedaan semantis, misalnya makna saung sebagai rumah utama. Sebaliknya, Bahasa Sunda Priangan memperlihatkan kecenderungan modernisasi dan kodifikasi melalui penggunaan bentuk baku serta dipengaruhi lebih kuat oleh Bahasa Indonesia. Ditemukan pula perbedaan fonologis (pemanjangan vokal), morfologis (penggunaan bentuk turunan tradisional), sintaksis (penghilangan subjek/objek), serta tingkat interferensi bahasa Indonesia yang berbeda antar kedua komunitas. Faktor sosiokultural yang memengaruhi variasi ini meliputi isolasi geografis Baduy, keterikatan pada tradisi, norma kesantunan, serta keterbukaan Priangan terhadap pendidikan modern dan interaksi eksternal. Secara keseluruhan, pilihan leksikal berfungsi sebagai penanda identitas: komunitas Baduy mempertahankan konservatisme linguistik sebagai bentuk resistensi terhadap homogenisasi, sedangkan komunitas Priangan menampilkan adaptasi terhadap modernitas. Temuan ini berkontribusi pada kajian variasi Sunda, linguistik kontak, dan ekolinguistik, sekaligus mendukung upaya pelestarian dialek yang terancam punah.